The right to life and the battle over children’s life: baby Charlie Gard in perspective (2017)
The Convention of the Right of the Child provides that every child has an inherent right to life. This means the child has a right to survival and development. Parents of a child have the responsibility, rights and duties to take "appropriate direction and guidance in the exercise by the child of the rights recognized in the Convention" The Government has the responsibility to ensure that the rights of a child are respected protected and fulfilled. Article 3 of the Convention states that the best interests of the child shall be a primary consideration in all actions taken on behalf of a child. The paper considered the case of baby Charlie Gard, a baby boy, born in the United Kingdom on 4 August 2016, with a genetic defect resulting in a rare disease and the battle between the parents, the hospital where he was being treated for the rare disease and the court. The paper further examined, who amongst, the three, complied with Article 3 of the Convention in the legal battle. The paper also considered who had the right to decide whether Baby Charlie would live or die. The paper provided the position, in Nigeria, under the Childs Rights Act, if baby Charlie were a Nigerian child